Application of calixpyrrole modified silica for the removal of 4-chlorophenol from aqueous media - Abbas, Ismail Ibrahim; El Hamaoui, Bassem Mohamad Riad; Najmeddine, Hilal Mohamad Jamal (European Journal of Chemistry, 2019)
In this research, calixpyrrole modified silica (III) was synthesized and characterized by Fourier transform infrared spectroscopy (FTIR), thermal gravimetric analysis (TGA) and scanning electron microscope (SEM) techniques. The synthesized material was used as an extractant for the removal of 4-chlorophenol from aqueous solution. Its efficiency was examined through both batch and column extraction methods. The effects of temperature, pH, initial chlorophenol concentration and mass of the adsorbent were examined using removal efficiencies. Initial concentration and quantity of adsorbent show a noticeable influence on the uptake capacity of the adsorbent. The kinetics and thermodynamics of chlorophenol removal from aqueous media were also investigated. Kinetic studies indicated that the extraction data can be best represented by pseudo second order model. Column extraction data were analyzed through Thomas, Yoon-Nelson and Yan et al. models to calculate kinetic coefficients and maximum sorption capacity of the modified silica (III). The adsorbent silica was regenerated by acid treatment without changing its properties.